ANALYSIS OF HIGHER-ORDER THINKING SKILLS (HOTS) ITEMS IN SENIOR HIGH SCHOOL ENGLISH NATIONAL EXAMINATION 2019 - Nurul Wahyuni Ilham; Baso Jabu; Chairil Anwar Korompot (ELT Worldwide: Journal of English Language Teaching, 2020)
In order to fulfill the 21’st century skills, the implementation of HOTS items to enhance students’ reasoning skills is deemed important. Nonetheless, we need to observe more about the extent and specific dimensions of HOTS applied in the English National Examination in Indonesia. The present study, therefore aimed to classify the items that fulfilled the indicators of HOTS items in ENE 2019 and specific dimension of knowledge types and dimension of cognitive process skills of the HOTS items. The results showed there was a sufficient total of a HOTS item in ENE 2019. Out of 35 questions, 15 (42.86%) were considered as HOTS items. The second finding was the dimension of cognitive process skills were on the stage of Analyze and Create. The findings indicated that ENE 2019 already had sufficient amount of HOTS items, although the distribution of the cognitive abilities is still monotonous. It was suggested for the exam developers to implement adequate proportion of the HOTS cognitive abilities to enhance students’ HOTS.